Microstructural Evolution and Micro‐Compression in High‐Purity Copper Processed by High‐Pressure Torsion1 . Issue 2 (17th November 2015) - Li, Jianwei; Xu, Jie; Wang, Chuan Ting; Shan, Debin; Guo, Bin; Langdon, Terence G.
Abstract : Pure copper is subjected to severe plastic deformation at room temperature using quasi‐constrained high‐pressure torsion through 1/4 to 10 turns. The evolution of the microstructure is monitored using X‐ray diffraction and electron backscatter diffraction. Specimens are analyzed both before and after micro‐compression of ≈50%. The results show that after 10 turns there is a homogeneous ultrafine‐grained (UFG) microstructure with an average grain size of ≈250 nm and with a simple shear texture. The micro‐compression testing shows that UFG specimens exhibit a better surface quality after compression thereby demonstrating an excellent potential for using UFG copper in micro‐forming. Abstract : Microstructural evolution and micro‐compression are investigated in pure copper processed by HPT . Microstructures are measured by EBSD and X‐ray diffraction. The ultrafine‐grained specimens produced by HPT exhibit a better surface quality after compression thereby suggesting there is an excellent potential for using this material for applications in micro‐forming technology.